Peptidylarginine Deiminases 2 Mediates Caspase-1-Associated Lethality in Pseudomonas aeruginosa Pneumonia-Induced Sepsis. (30th July 2020) - Wu, Zhenyu; Tian, Yuzi; Alam, Hasan B; Li, Patrick; Duan, Xiuzhen; Williams, Aaron M; Liu, Baoling; Ma, Jianjie; Li, Yongqing
Abstract: Background: Pseudomonas aeruginosa (PA) is a pathogenic bacterium that causes severe pneumonia in critically ill and immunocompromised patients. Peptidylarginine deiminase (PAD) 2, PAD4, and caspase-1 are important enzymes in mediating host response to infection. The goal of this study was to determine the interplay between PAD2, PAD4, and caspase-1 in PA pneumonia-induced sepsis. Methods: Pneumonia was produced in wild-type, Pad2 −/−, and Pad4 −/− mice by intranasal inoculation of PA (2.5 × 106 colony-forming units per mouse), and survival (n = 15/group) was monitored for 10 days. Bone marrow-derived macrophages (BMDMs) were isolated for in vitro studies. Samples were collected at specific timepoints for Western blot, bacterial load determination, and flow cytometry analysis. Results: Caspase-1-dependent inflammation was diminished in PA-inoculated Pad2 −/− mice, contributing to reduced macrophage death and enhanced bacterial clearance. In addition, Pad2 −/− mice exhibited improved survival and attenuated acute lung injury after PA infection. In contrast, Pad4 −/− mice did not display diminished caspase-1 activation, altered bacterial loads, or improved survival. Conclusions: Peptidylarginine deiminase 2 plays an essential role in the pathogenesis of pulmonary sepsis by mediating caspase-1 activation. This goes against previous findings of PAD4 in sepsis. Our study suggests that PAD2 is a potential therapeutic target of PA pneumonia-induced sepsis. Abstract : Pad2 −/− mice exhibited improved survival, attenuated lung injury, and enhanced bacterial clearance during Pseudomonas aeruginosa pneumonia-induced sepsis. The protective effects are probably associated with the regulatory effects of PAD2 on caspase-1-dependent pyroptosis.